A SEM study of the reindeer sinus worm (Linguatula arctica) - Sven Nikander; Seppo Saari (Rangifer, 2009)
Pentastomids are a group of peculiar parasitic arthropods, often referred to as tongue worms due to the resemblance of some species to a tongue. Linguatula arctica is the sinus worm of the reindeer (Rangifer tarandus), being the only pentastomid to have a direct life cycle and an ungulate as a definite host. Here, the surface structures and internal anatomy of adult L. arctica are described as seen by scanning electron microscopy (SEM). Sinus worms were collected in the winter 1991-92 in Finnish Lapland. Paranasal cavities of about 80 reindeer were examined and 30 sinus worms were found. The sinus worms had typical Linguatula sp. morphology, being paddle-shaped, transparent, pale yellow, dorsoventrally flattened and pseudosegmented with a long tapering end. Present at the anteroventral part of the cephalothorax was an oral opening with a large, conspicuous, head-like papillar structure. Bilaterally, on both sides of this opening, was a pair of strong curved hooks. The cephalothorax and abdomen had a segmented appearance, as they showed distinct annulation. There was a small cup-shaped sensory organ present at the lateral margin on each annula. The posterior edge of each annula was roughened by tiny spines projecting backwards. Throughout the cuticular surface, small, circular depressions that represented the apical portion of chloride cells. The genital opening of the male was located medioventrally between the tips of the posterior pair of hooks, and that of the female posteroventrally and subterminally. In both sexes, the genital opening was bilaterally flanked by papillar (in males) or leaf-like (in females) structures. One copulating couple was present, with the male attached to the posteroventral part of the female with its anteroventral hooks and papillae. Several structures typical of arthropods and other pentastomids were identified. Because SEM allows only surfaces to be studied, the morphology and especially the sense organs of L. arctica remain obscure. Transmission electron microscopy should be employed to gain more information about this fascinating creature and its origin.